METANARASI DALAM TEKS BRAHMA SŪTRA - Suryana, Adi; Subagia, I Nyoman; Brahman, I Made Adi (Pangkaja: Jurnal Agama Hindu, 2024)
As a human being who lives in a world full of great secrets of the universe, surely the investigation of metaphysics is interesting. Metaphysical matters can generally be sought through sacred texts as well as academic reasoning. Therefore, metanarratives formed from metaphysical objects are a matter that dancing to be discussed. Moreover, a deep understanding of the nature of these metaphysical objects will help humans discover things that are still hidden in the universe. The events shown in the universe can certainly be accessed through various sources, one of which is scripture. In this context, Brahma Sūtra as one of the sacred texts of Hinduism has a metanarrative in which it contains explanations of metaphysical objects that are interesting to discuss. This discussion includes the concepts of Brahman, atman and spirit, mind, prāņa, and mokșa. Some metanarratives in this study will be elaborated scientifically through the study of Hindu Theology, of course, by including various text sources in the Brahma Sūtra. The method used is Qualitative with a Descriptive approach used to analyze the text of the Brahma Sūtra. From this study it can be seen that Brahman is the One True God who is the supreme entity of the entire universe. The Atma and spirit are the parts of Brahman that must seek to return to Brahman after death. The mind is the means of accessing the universe as well as the access of Brahman consciousness. Prāņa is the energy or vital force of living beings used as a means of accessing Brahman consciousness. Prāņa is the energy or vital force of living beings used as a means of accessing Brahman consciousness. The last is mokșa, the ultimate goal of living beings which is the highest consciousness/freedom.